2017
DOI: 10.4172/2150-3494.1000174
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Catechin and Gallic Acid from Colombian Bark of Pinus patula

Abstract: Pine bark is a rich source of natural polyphenols, compounds which have attracted increasing attention in the fields of nutrition, health and medicine. Extractive components include large amounts of phenolic compounds. The ethanolic extract was obtained from Pinus patula bark grown in the forests of the Cauca Department in Colombia South America. The Gallic acid, catechin, epicatechin and procyanidin B2 contents in ethanolic extract were 3.12, 1.99, 0.80, and 0.71%, respectively, these compounds were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…FTIR spectrum for GA powder exhibits characteristic peaks at 3482 cm −1 and 3281 cm −1 , which are due to stretching of the O-H groups (not shown), a sharp absorption band of carboxylic group -COOH at 1695 cm −1 , absorption bands of -OH at 866 cm −1 , as well as -C-OH at 1320 cm −1 , 1375 cm −1 (Phenol (or) tertiary alcohol, OH bend), 1244 cm −1 (C-O stretch) and peak at 766, 1021, 1100, and 1614 cm −1 , a C=C stretching vibration can be observed at 1539 cm −1 [41]. The peaks located at 1614, 1539, 1446 cm −1 represented the aromatic ring C=C stretching vibrations [42].…”
Section: Ga and Qc Characterizationmentioning
confidence: 99%
“…FTIR spectrum for GA powder exhibits characteristic peaks at 3482 cm −1 and 3281 cm −1 , which are due to stretching of the O-H groups (not shown), a sharp absorption band of carboxylic group -COOH at 1695 cm −1 , absorption bands of -OH at 866 cm −1 , as well as -C-OH at 1320 cm −1 , 1375 cm −1 (Phenol (or) tertiary alcohol, OH bend), 1244 cm −1 (C-O stretch) and peak at 766, 1021, 1100, and 1614 cm −1 , a C=C stretching vibration can be observed at 1539 cm −1 [41]. The peaks located at 1614, 1539, 1446 cm −1 represented the aromatic ring C=C stretching vibrations [42].…”
Section: Ga and Qc Characterizationmentioning
confidence: 99%
“…The LC-MS/MS analysis of a methanol extract of Corn cobs (Zea mays L.) indicated the presence of bioactive flavonoids (catechin; kaempferol 3-arabinofuranoside 7-rhamnoside; 6,8-Di-C-beta-Darabino pyranosyl apigenin; 5,7-Dihydroxy-8,4'-methoxyisoflavone) (table 2). Catechins have been widely isolated from several plants [28][29][30][31], and it has been reported that catechin has antioxidant [32] and anti-skin aging activities [33]. The kaempferol group and its glycoside derivatives have several activities, such as antioxidants [34,35] and anti-aging [36].…”
Section: Discussionmentioning
confidence: 99%
“…Given the existence of the other procyanidin dimers and trimers which were not quantified, the content of procyanidins in PBE may be similar or greater than in other species ( Table 2 ). (+)-Catechin concentration was 10.08 mg/g in PBE, which showed similar or higher amounts than the bark of other Pinus species, 11.4 mg/g for P. radiata [ 22 ], 19.9 mg/g for P. patula [ 23 ], 8.4 mg/g for P. sylvestris , and 0.6 mg/g for P. nigra [ 24 ].…”
Section: Discussionmentioning
confidence: 99%